The Sale of Joseph in Genesis 37:18–26: Narrative Cohesion and Coherence - McAffee, Matthew (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2024)
The purpose of this discussion is to assess the ability of the Documentary Hypothesis to provide a compelling reading of Genesis 37. Is the literary reconstruction of the J/E source divisions able to offer a compelling, internally consistent text? As a counter proposal, I consider the framework of coherence theory as a means of evaluating the central claim of documentarians that Genesis 37 lacks compositional cohesion and coherence. The method of this discussion takes the following course. First, I sketch out a brief overview of the various compositional approaches to Genesis 37 and its place in the Joseph story. Second, I consider the nature of narrative cohesion and coherence and how these concepts inform one’s reading of Genesis 37, arguing that the markers of cohesion embedded in the narrative provide a means of guiding the reader coherently through the twists and turns of the plot line. Third, I highlight several narrative links that cross proposed source boundaries, functioning as linguistic signals for cohesion, and that suggest literary coherence. Fourth, I re-assess the so-called Ishmaelite/Midianite problem that has served a central role in most source divisions of Genesis 37.